Correlation between salivary zinc levels and salivary volume on taste disorders in elderly patients - Dewi Kania Intan Permatasari; Tenny Setiani Dewi; Dewi Marhaeni Diah Herawati (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Taste disorders often occur in the elderly, which can have serious consequences on their health status. Zinc and saliva volume have a role in maintaining taste acuity, especially in the elderly. Purpose: This study was to determine the correlation between salivary zinc levels, salivary volume, and taste disorders in elderly patients. Methods: This was a cross-sectional research. Elderly patients with and without taste disorders were included in this study. Salivary zinc levels were measured using the Atomic Absorption Spectrometry (AAS) method. Salivary volume was measured using the spitting method. The correlation between salivary zinc levels, salivary volume, and taste disorders was analysed using the chi-square test. Multivariate analysis was performed to control for confounding variables with logistic regression. Results: Based on our findings, no significant correlation was determined between the levels of zinc in saliva and taste disorders. However, there was a significant correlation between salivary volume and taste disorders. Salivary volume and smoking were determined to be associated with taste disorders. Conclusion: This research showed that salivary zinc levels were not correlated with taste disorders; on the contrary, salivary volume was correlated with taste disorders. Smoking was determined to be a confounding variable on taste disorders in elderly patients.